Balance and Mobility Dysfunctionand Falls Risk in Older People with Mild to Moderate Alzheimer Disease - Suttanon, P.; Hill, Keith; Said, C.; LoGiudice, D.; Lautenschlager, N.; Dodd, K. (Lippincott Williams and Wilkins, 2011)
Objective: This study aimed to identify the magnitude and type of balance and mobility impairments in people with Alzheimer disease by comparing their performance with that of older people without cognitive impairment. Design: Twenty-five community-dwelling people with mild to moderate Alzheimer disease and a comparison group of 25 cognitively intact age- and sex-matched people completed a comprehensive balance and mobility assessment. This included computerized posturography measures of static and dynamic balance under various conditions, clinical balance, and mobility measures, and measures of falls and falls risk. Results: The level of falls risk was higher in people with Alzheimer disease. Standing balance in people with Alzheimer disease was significantly impaired across a range of static and dynamic balance conditions. Activity level, gait, and mobility measures were also impaired, particularly turning and dual tasks. Conclusions: The findings of the study highlight the value of including balance screening as a routine component of early dementia assessment. This would allow for the early detection of balance dysfunction and the introduction of balance retraining before impairments progress to more advanced levels.